The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/03014223.2012.711334
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aerial application of 1080 cereal baits on radio-tagged South Island fernbirds (Bowdleria punctata punctata)

Abstract: In New Zealand, the toxin sodium fluoroacetate (compound 1080) is used to reduce numbers of introduced brushtail possums (Trichosurus vulpecula) to enhance forest condition and reduce bovine tuberculosis (Tb) infection in livestock. However, there is concern that the use of toxins may cause mortality in non-target species. We investigated the effect of possum control using aerially applied cereal baits containing 1080 on 36 radio-tagged South Island fernbirds (Bowdleria punctata punctata) in winter 2010. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Changes to bait type, concentration, and pre-feeding practices are considered to have reduced the effects on non-target species. More recent studies have found that aerial 1080 operations have no direct impacts on a range of taxa, including bird populations (Greene et al 2013;Schadewinkel et al 2014), or that a small level of immediate mortality can be outweighed by subsequent increased survival and breeding success in the absence of predators (van Klink et al 2013;Elliott & Kemp 2016). However, much of the research on 1080 impacts has focused on birds of conservation concern including kākā (Nestor meridionalis; Moorhouse et al 2003;Powlesland et al 2003), kiwi (Apteryx spp.…”
Section: Introductionmentioning
confidence: 99%
“…Changes to bait type, concentration, and pre-feeding practices are considered to have reduced the effects on non-target species. More recent studies have found that aerial 1080 operations have no direct impacts on a range of taxa, including bird populations (Greene et al 2013;Schadewinkel et al 2014), or that a small level of immediate mortality can be outweighed by subsequent increased survival and breeding success in the absence of predators (van Klink et al 2013;Elliott & Kemp 2016). However, much of the research on 1080 impacts has focused on birds of conservation concern including kākā (Nestor meridionalis; Moorhouse et al 2003;Powlesland et al 2003), kiwi (Apteryx spp.…”
Section: Introductionmentioning
confidence: 99%
“…Nontarget poisoning may occur as primary poisoning, where non-target species directly consume poisoned baits; or as secondary poisoning, where non-target species consume prey or carcasses that have fed on baits (Eason et al, 2013a;Lloyd & McQueen, 2000). However, the benefits gained by non-target species through reduced predation pressure and/or reduced competition after aerial 1080 operations are generally considered to outweigh any such losses (van Klink et al, 2013). It is important that the potential losses and benefits of non-target species in areas destined for 1080 treatment are well understood.…”
Section: Introductionmentioning
confidence: 99%